Association Of Food And Drug Allergy With Antituberculosis Drug Related Hepatitis Or Skin Reactions: A Case Control Study (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2014)
Introduction: Anti-tuberculosis drugs can cause adverse reactions including hepatitis and skin reactions. This case control study was aimed at fi nding out whether allergy to drug or food acts as a risk factor for the development of anti-tuberculosis drug induced hepatitis or skin reactions. Patients with tuberculosis on category 1 regimen, who presented to the Teaching Hospital Kandy Sri Lanka, due to anti-tuberculosis drug induced hepatitis or skin reactions from 1st July 2010 to 30th June 2011 were recruited. Methodology: Patients with drug induced hepatitis or skin reactions were grouped as cases and patients who didn’t develop hepatitis or skin reactions during the treatment period were selected as controls. Controls were matched for age, gender, weight, and consumption of alcohol. Cases and controls were inquired for the presence of allergy to drugs or food. Two groups were compared using odds ratio. Results: There were 61 cases [33 (54.1%) males, 28 (45.9%) females] and 61 controls .Ten patients (16.39%) among the cases had allergy to food or drugs while in control group only 2 (03.2%) had allergy. Odds ratio for the development of drug reactions in patients with a history of allergy was 5.8 (confi dence interval 1.2 to 27.6). Conclusion: Patients with allergy to drugs or foods have 5.8 times risk of developing anti-tuberculosis drug induced hepatitis or skin reaction. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2013; X(2); 48-53 DOI: http://dx.doi.org/10.3126/saarctb.v10i2.9714